Relationship between Knowledge and Attitudes Regarding Preventive Behaviors for Sexually Transmitted Infections Among Prisoners in Ambon City’s Women's Correctional Institution - Zahra Hansuri; Fauzan Tuankotta; Fathiyatul Khair; Alessandra Flowrence Saija; Amanda Gracia Manuputty (Fakultas Kedokteran Universitas Sriwijaya, 2026)
Sexually transmitted infections (STIs) are diseases that are transmitted through sexual intercourse, whether vaginal, anal, or oral. STIs cases specifically target key groups such as FSWs (female sex workers), MSM (men who have sex with men), WSW (women who have sex with women), injecting drug users and prisoners in correctional institutions who are closely related to risky sexual behavior. Risky sexual behavior in these groups is often caused by low knowledge about the dangers and impacts of STIs. Preventing the transmission of STIs is very important to control their spread. Good knowledge and attitudes about STIs can improve effective preventive behaviors. This research aims to determine the relationship between knowledge and attitude towards STIs prevention behavior in Ambon City’s Class III Women's Correctional Institution. This research used a cross-sectional design with a total sampling technique, involving 68 female inmates. Data were collected through a questionnaire containing questions about knowledge, attitudes, and STIs prevention behavior. The results showed that 44 respondents (64.7%) had good knowledge of STIs, 50 respondents (73.5%) had a supportive attitude towards STIs, and 58 respondents (85.3%) had good STIs prevention behavior. The results of bivariate analysis using the Fisher exact test showed a significant relationship between knowledge and prevention behavior (p=0.003) and between attitude and STIs prevention behavior (p=0.017). Good knowledge and attitudes towards STIs correlate with better prevention behaviors. Therefore, it is important to improve knowledge and attitudes that support STIs prevention in prisons.